JOURNAL OF GOVERNMENT & POLITICS : The Influence of Social Media Towards Student Political Participation During the 2014 Indonesian Presidential Election - Anwar Kholid , Rahmawati Husein (FISIPOL UMY, 2015)
This research attempts to examine the political participation of social media users particularly of Facebook and Twitter during the 2014 Indonesian presidential election